Governance in the sergested shrimp (Acetes spp.) industry in the Philippines the case of Oton, Iloilo - Burgos, Roel C (Miagao, Iloilo University of the Philippines Visayas, 2011)
The sergested shrimp (Acetes spp.) industry in various places in Philippines provides different lessons and experiences but studies in this field especially its governance is given less attention and priority. In the Municipality of Oton, this industry is one of the major economic activities because it provides substantial contribution to the livelihood of fisher folks and additional revenue for the municipality. This paper describes the sergested shrimp (hipon) industry in Oton including its catching, processing and marketing operations. The role/participation of the actors involved in the industry were also identified and the existence of governance characteristics in the hipon industry was assessed and characterized. Relationships between actors wee evaluated by the presence or absence of good governance characteristics using the characteristics described by the United Nations Economic and Social Commission for Asia and the Pacific (UNESCAP). Issues and concerns affecting the hipon industry in Oton were also identified. Focus group discussions and key informant interview were done to gather all the necessary data as well as to capture views and opinions of the industry players including stte (LGU-Oton), market and civil society groups. survey was also conducted to determine the existence of governance characteristics in the hipon industry. Although hipon industry in Oton is still in the lerning stage with only seven years of operation, results of the study shows that is lready a flourishing one. The management of the industry is more of an authoritarian/hierarchical type wherein most of the initiatives come from the state; however active participation from ll actors was encouraged. Certain concerns were revealed by industry players with transparency between broker and operators as the most discussed issue. Responsiveness of the state to the concerns of other industry players was also brought up. Recommendations were made and suggested to the local government for policy adoption to support and develop a robust shrimp industry without sacrificing the sustainability of hipon supply.
Special Problem (MMA) -- University of the Philippines Visayas, 2011.
Keywords: Sergested shrimp industry -- Oton, Iloilo